DEVELOPING STUDENT RELATIONSHIPS WITH HUMAN VALUES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article aims to develop in students a positive attitude towards universal values, to study the problems associated with the origin of human culture, the tradition of cultivating universal values, the ability to live among people on the basis of laws such as kindness, justice, love - that is, universal values. is devoted to the study of all the information included in the concept, as well as the problems posed by man, the formation of his personality, the priority of education, development and education.